2017
DOI: 10.1016/j.tcb.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Axonal Energy Homeostasis and Mitochondrial Trafficking and Anchoring

Abstract: Mitochondria are key cellular power plants essential for neuronal growth, survival, function, and regeneration after injury. Given their unique morphological features, neurons face exceptional challenges in maintaining energy homeostasis at distal synapses and growth cones where energy is in high demand. Efficient regulation of mitochondrial trafficking and anchoring is critical for neurons to meet altered energy requirements. Mitochondrial dysfunction and impaired transport have been implicated in several maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
155
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(158 citation statements)
references
References 87 publications
(138 reference statements)
1
155
2
Order By: Relevance
“…Disorders that more broadly affect axonal transport, such as tauopathies and SOD1 mutations, may include phenotypes with a significant mitochondrial etiology (De Vos et al, 2008; Millecamps and Julien, 2013). More recently changes in mitostatic processes also have been described during neuroinflammation (Sadeghian et al, 2016; Sorbara et al, 2014; Witte et al, 2014) and after neurotrauma (Cartoni et al, 2016; Han et al, 2016; Sheng, 2017; Zhou et al, 2016). Such links to pathology rightly spur interest in understanding mitostasis.…”
Section: Introduction: Mitostasis In Neuronsmentioning
confidence: 99%
“…Disorders that more broadly affect axonal transport, such as tauopathies and SOD1 mutations, may include phenotypes with a significant mitochondrial etiology (De Vos et al, 2008; Millecamps and Julien, 2013). More recently changes in mitostatic processes also have been described during neuroinflammation (Sadeghian et al, 2016; Sorbara et al, 2014; Witte et al, 2014) and after neurotrauma (Cartoni et al, 2016; Han et al, 2016; Sheng, 2017; Zhou et al, 2016). Such links to pathology rightly spur interest in understanding mitostasis.…”
Section: Introduction: Mitostasis In Neuronsmentioning
confidence: 99%
“…Kinesin and cytoplasmic dynein motors drive axonal mitochondria for anterograde and retrograde transport, respectively (Birsa et al, 2013; Saxton and Hollenbeck, 2012; Schwarz, 2013; Sheng, 2014, 2017). Our previous studies identified syntaphilin (SNPH) as a static anchor that immobilizes axonal mitochondria through its mitochondria-targeting sequence and microtubule-anchoring domain (Chen et al, 2013; Kang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As ATP diffusion is not effective over the long distances of neuronal processes (Hubley, Locke, & Moerland, ; Sun, Qiao, Pan, Chen, & Sheng, ), neurons require specialized mechanisms to maintain energy homeostasis throughout the cell, particularly in distal axons that can extend several centimeters to several feet long for some peripheral nerves (Saxton & Hollenbeck, ). Precisely how neurons sense and respond to dynamic changes in energy demand during rest, activation, growth, and in pathological conditions is still being elucidated (Sheng, ). However, considering that mitochondrial dysfunction is associated with numerous neurodegenerative diseases (Pathak, Berthet, & Nakamura, ; Sheng & Cai, ), determining if and when bioenergetic failure in distal axons contributes to neuronal pathology is highly clinically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…A continuous supply of ATP is essential for cell growth, survival, and function in the brain, with synapses being the primary sites of ATP consumption (Attwell & Laughlin, ; Harris, Jolivet, & Attwell, ; Lennie, ; Nicholls & Budd, ; Sheng, ). Within neurons, ATP is primarily generated by the complete oxidation of glucose to carbon dioxide (CO 2 ) and water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation